(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
In contemporary psychology and pedagogy, the concept of sanogenic thinking has gained increasing attention as an approach aimed at promoting psychological health, emotional stability, and constructive cognitive patterns. The term “sanogenic” originates from the Latin sanus (healthy) and refers to thinking processes that contribute to mental well-being, resilience, and the reduction of destructive emotional responses. The development of sanogenic thinking is closely associated with the works of both classical and modern foreign scholars in psychology, cognitive science, and humanistic education. Their theories provide a strong scientific foundation for understanding how individuals can transform negative emotional experiences into constructive cognitive and behavioral strategies.